Viral Hell: Central-European Dystopian Visions of Social Media - Filipowicz, Marcin (Porównania, 2021)
Over the past decade, many democratic countries have been caught off guard by their own unpreparedness in dealing with the threats associated with the spread of social media. Surveillance, disinformation, propaganda or hate speech have all become real threats caused by the largest social media platforms. Literature has also reacted to this phenomenon, most notably by providing dystopian visions of the further uncontrolled impact of social media. The analysis focuses on two novels recently published in the field of Czech and Slovak literatures—the first one by Czech writer David Zábranský Logoz or Robert Holm a Danish Marketer (2019) and the second one by Slovak writer Michal Hvorecký Troll (2017). The core aim of the analysis is to search for an answer to the question whether the literature limits itself only to descriptions of apocalyptic visions, or whether it shows possible recovery plans.